Thermogravimetric and kinetic analyses of oil palm empty fruit bunch (OPEFB) pellets using the distributed activation energy model - Nyakuma, B. B. (Penerbit Universiti Sains Malaysia, 2016)
The thermal degradation behaviour and decomposition kinetics of oil palm empty fruit bunch (OPEFB) pellets were investigated using a thermogravimetric analyser and the distributed activation energy model (DAEM). The OPEFB pellets were heated from 30°C to 1000°C at three different heating rates (5, 10, 20°C min-1) under a nitrogen atmosphere. The thermogravimetric-derivative thermogravimetric (TG-DTG) curves revealed that the non-isothermal decomposition of OPEFB pellets occurred in the following three stages: drying (35°C-175°C), active pyrolysis (200°C-370°C) and passive pyrolysis (370°C-1000°C), which resulted in the loss of moisture, volatile matter and char, respectively. The distributed activation energy model was subsequently used to determine the apparent activation energies (E) and pre-exponential factors (A), which ranged from 37.89 kJ mol-1 to 234.05 kJ mol-1 and from 2.05 × 102 min-1 to 3.54 × 1018 min-1, respectively, for conversions of α = 0.05-0.70 during the thermal degradation. The wide E and A distributions obtained from the kinetic analysis are attributed to the complex chemical reactions of pyrolysis. The kinetic analysis revealed the kinetic compensation effect (KCE), with the highest E and A values occurring in the range of α = 0.2-0.4. This result indicates that the active pyrolysis stage is the rate-determining step during the thermal decomposition of OPEFB pellets.